Financial And Legal Obstacles And Small And Medium Firm Performance: Evidence from Middle Income East Asian - Anh Tuan Bui; Linh Chi Pham; Thi Khanh Van Ta (Global Labor Organization (GLO), 2021)
This paper explores the impact of financial and legal obstacles that affect small and medium enterprises (SMEs) in middle-income East Asian countries by utilizing the most recent and unique dataset from the World Bank Enterprise Surveys. We particularly assess whether and at what level the effects on SMEs differ from those on large firms; We also examine how financial and institutional development levels contribute to firm performance. Our findings provide important guidance for regulators, including the authorities of middle-income nations, who seek to facilitate SMEs' development.
Keywords: G38; G01; G00; 330; Sales Growth; Employment Growth; Financial Obstacles; Legal Obstacles